EXPANSION OF THE READING SPACE BUILDING TO IMPROVE THE QUALITY OF EDUCATION FOR COMMUNITY CHILDREN BELAWAN NELAYAN - Siregar, Riza Inanda; Karolina, Rahmi; Handana, Muhammad Agung Putra; Syahrizal (Talenta Publisher, 2018)
The condition of the reading hut, which only has the pillars of non-structural wood which has a short wooden life, requires the community to periodically replace the rotten wood pillars. Of course this will take a lot of time and costs. Children and adults at the service location have good reading interests. They routinely visit the floating reading hut, but lately people's interest has diminished because the condition of the floating library is not feasible. The woods of the floating library building are decayed and not suitable to be occupied. Especially the foundation or pillar of the building can no longer be able to survive firmly. These things are the background of the community service activities team to choose the location to be able to apply civil engineering in making foundation or as a pillar of the floating library building of Belawan Fishermen's Village. The main thing and priority that becomes the problem in theFishermen Village which is the service partner is the reading hut that is used by the children of the Belawan Fishermen Village whose capacity is inadequate. The reading lodge does not have a terrace that can be used by local children to play and learn. In addition, the terrace can be used to prevent rainwaterfrom entering the main room of the reading cottage. The solution offered in this program is the expansion of the reading hut in the form of a decent terrace to be used by the children of the Belawan Fishermen Village community to learn and play. The expansion of the reading hut consists of concrete pile foundations and floor plates from wooden planks or plywood boards with zinc roofs.